The Translation of Passive Voice in Harry Potter Novel into Bahasa Indonesia - Harry Sumbayu; Amrin Saragih; Syahron Lubis (LINGUISTIK TERAPAN, 2015)
This study addresses the translation of passive voice in Harry Potter and the Prisoner of Azakaban into Bahasa Indonesia. The study was based on descriptive qualitative approach. The data were collected by applying documentary techniques. There were three chapters taken as the source of the data. They were chapters 1, 8 and 15. The findings indicated that there were two types of passive voices as a product of passive voices’ translation in Bahasa Indonesia. The passive voice retained as passive one in TL was more dominantly translated into passive voice type one than type two in TL. It caused the use of prefix di+verb base, prefix di+verb base suffix i, and prefix di +verb base+ suffix+ kan are able to represent the meaning of the SL literally and culturally. The changing of English passive voice into Bahasa Indonesia active voice when they were translated indicated that the translator has attempted to find the closest natural equivalent of the source language in aspect of grammar, style, and cultural value. In essence naturalization rate of an expression is a matter of looking for matches in level lexical categories, grammatical categories, semantic, and cultural context.   Key words: translation, passive voice, English, Bahasa Indonesia.